(u-3)*9=18

Simple and best practice solution for (u-3)*9=18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (u-3)*9=18 equation:


Simplifying
(u + -3) * 9 = 18

Reorder the terms:
(-3 + u) * 9 = 18

Reorder the terms for easier multiplication:
9(-3 + u) = 18
(-3 * 9 + u * 9) = 18
(-27 + 9u) = 18

Solving
-27 + 9u = 18

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '27' to each side of the equation.
-27 + 27 + 9u = 18 + 27

Combine like terms: -27 + 27 = 0
0 + 9u = 18 + 27
9u = 18 + 27

Combine like terms: 18 + 27 = 45
9u = 45

Divide each side by '9'.
u = 5

Simplifying
u = 5

See similar equations:

| 20y - 16 = 18y - 9 | | -9a+4=24 | | (q-6)*2=18 | | 5p + 7 = 3( 4 - p ) | | y=1/3bh | | 7r + 2 = 5( r - 4 ) | | 7p + 2 = 5p + 8 | | 8x^2+8x+10=0 | | 5g+4f-2f+3g= | | f(x)=-16x^2+50x-25 | | 7r + 3 = 3( r - 1 ) | | 6p - 5 = 2p + 7 | | 12a + 2 = 2a - 6 | | (6x-5)(x-3)=2x(3x+4) | | sqrt(5x+1)-sqrt(4x+3)=x | | 6z^3-7z^3-3z=0 | | Y/4-5=2 | | 9x^2y-4y= | | 13-b=4 | | 29-x =x+5 | | 4x+1.5y=9 | | 29-x =x+5 | | -4-1=3 | | 2q=w | | 4cosx/2=0 | | 5x+8(1.3-x)=8 | | x/3-2=-1 | | 2x+16=x+29 | | 2x+76=776 | | Tan18=12/x | | 2x+72=822 | | 8x-7=103-x |

Equations solver categories